Ecología política del nexo agua-energía-alimentos en dos cuencas transfronterizas: Alto Putumayo y Mira-Mataje - Forero, Jorge Enrique (2025)
This article examines the dynamics of the Water-Energy-Food nexus in two transboundary basins between Ecuador and Colombia, from a political ecology perspective that prioritizes experiences and perspectives of local communities. Through in-depth interviews, emerging categories are identified: territory, community, extractivism and conflict. Communities experience extractive activities as a threat to their territory, culture and ways of life. Water pollution, decreased availability and climate changes negatively impact agriculture and food security. The proposed approach reveals the struggles for environmental justice and power inequalities in the region. The most affected communities are indigenous, Afro-descendant and peasant communities. The recovery of traditional culture and food sovereignty are presented as key strategies to resist and adapt to the negative effects of extractivism and the climate crisis.